Comparative evaluation of aqueous humor viscosity. (27th January 2014) - Davis, Kyshia; Carter, Renee; Tully, Thomas; Negulescu, Ioan; Storey, Eric
Abstract Objective To evaluate aqueous humor viscosity in the raptor, dog, cat, and horse, with a primary focus on the barred owl (Strix varia). Animals studied Twenty‐six raptors, ten dogs, three cats, and one horse. Procedure Animals were euthanized for reasons unrelated to this study. Immediately, after horizontal and vertical corneal dimensions were measured, and anterior chamber paracentesis was performed to quantify anterior chamber volume and obtain aqueous humor samples for viscosity analysis. Dynamic aqueous humor viscosity was measured using a dynamic shear rheometer (AR 1000 TA Instruments, New Castle, DE, USA) at 20 °C. Statistical analysis included descriptive statistics, unpaired t‐tests, and Tukey's test to evaluate the mean ± standard deviation for corneal diameter, anterior chamber volume, and aqueous humor viscosity amongst groups and calculation of Spearman's coefficient for correlation analyses. Results The mean aqueous humor viscosity in the barred owl was 14.1 centipoise (cP) ± 9, cat 4.4 cP ± 0.2, and dog 2.9 cP ± 1.3. The aqueous humor viscosity for the horse was 1 cP. Conclusions Of the animals evaluated in this study, the raptor aqueous humor was the most viscous. The aqueous humor of the barred owl is significantly more viscous than the dog (P < 0.0001). The aqueous humor viscosity of the raptor, dog, cat, and horse can be successfully determined using a dynamic shear rheometer.